Chronic renal failure and growth. Issue 4 (April 1989) - Rees, L; Rigden, S P; Ward, G M
Abstract : Growth was assessed in 38 prepubertal children with chronic renal failure for a mean (range) of 2.3 (1-4) years. At first clinic visit their mean (range) glomerular filtration rate was 17 (7-35) ml/min/1.73 m2, their mean (range) age was 3.4 (0.2-9.1) years, and 23 (61%) were greater than two standard deviations below the mean for height. After intensive medical management of their chronic renal failure, half of the children who presented before 2 years of age showed appreciable catch up growth. Only a slow improvement in growth occurred in most children presenting over 2 years of age. At final assessment, the mean (range) glomerular filtration rate was 15 (6-42) ml/min/1.73(2) and 20 (53%) were greater than two standard deviations below the mean for height. There was no correlation between glomerular filtration rate and growth. There remained a group of children who continued to grow poorly. Many of these were of low birth weight, and had dysplastic kidneys.